لغةُ الجمالِ في الشعرِ الصوفيِّ: شعرُ ابنِ سَوَّارِ الدمشقيِّ (603/677هـ) أنموذجًا (Damascus University Journal of arts and humanities sciences, 2024)
Ibn Siwar Al-Dimashqi (603AH/677AH) is considered one of the great figures of Sufism in the seventh century AH. He left us a wonderful legacy that is present between the two covers of his Diwan, in which are masterpieces of poetry that enrich the taste of the recipient with the finest art of rhetoric. We can describe the Diwan as a mecca of love and beauty, yet researchers in Sufi poetry have failed to give this poetry its due study and attention.          In the pages of this research, the language of beauty in Ibn Siwar's poetry was analyzed, and Al-Aster removed glimpses of beauty and splendor that were absent from people's minds during the era of pure materialism. Sufism’s interaction with beauty was ascending towards pure divine love and divine knowledge, which is the goal and goal of Sufism. Linking mysticism to beauty leads to the rise of the mystics in divine love. This love is the path to knowledge sought by the Sufis, including Ibn Suwar al-Dimashqi. This study aimed to monitor the interaction between beauty as a philosophical concept and Sufi poetry, and to show the extent to which each is affected by the other.        This research can be a key to studying Ibn Sewar's poetry according to different frameworks: rhetorical, linguistic, stylistic, and other approaches used in the study of Arabic poetry. The research ended with a set of results that resulted from serious research on Sufi poetry in general and Ibn Suwar’s poetry in particular.
Keywords: Sufi Poetry; Beauty and Love; Ibn Suwar al-Dimashqi; Divine Beauty; Language and Lexicon; Beauty and Majesty